1976
DOI: 10.1103/physrevlett.37.1705
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Temperature Dependence of the Magnetic Susceptibility of Quasi-One-Dimensional Metals

Abstract: The temperature dependence of the g values measured for the series of alloys (TSeF) x -(TTF) 1 _ X (TCNQ) (where TSeF is tetraselenafulvalene, TTF is tetrathiafulvalene, and TCNQ is tetracyanoquinodimethane), 0^*^0.68, in the temperature range 60 K Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is worth noting that resolved EPR lines have also be reported in HMTTF-TCNQ and HMTTF-TCNQF 4 (HMTTF stands for hexamethyl-TTF) Note that this decomposition technique implies that the line width is frequency independent as seen for TTF-TCNQ by Tomkiewicz et al Some frequency dependence of the EPR line width has however been reported later . Figure shows the susceptibility decomposition for TTF-TCNQ with the contribution of each kind of stacks and the total susceptibility which is consistent with the static result .…”
Section: 3 Ttf-tcnq and Related Charge Transfer Saltsmentioning
confidence: 99%
“…It is worth noting that resolved EPR lines have also be reported in HMTTF-TCNQ and HMTTF-TCNQF 4 (HMTTF stands for hexamethyl-TTF) Note that this decomposition technique implies that the line width is frequency independent as seen for TTF-TCNQ by Tomkiewicz et al Some frequency dependence of the EPR line width has however been reported later . Figure shows the susceptibility decomposition for TTF-TCNQ with the contribution of each kind of stacks and the total susceptibility which is consistent with the static result .…”
Section: 3 Ttf-tcnq and Related Charge Transfer Saltsmentioning
confidence: 99%
“…For (TMTTF)2BF4 this is comprehensible since g is a molecular property, and contracting the lattice one does not expect to change molecular quantities. In the case of TTF-TCNQ the constancy of g means more, since the molecular g-factors of each chain are mixed together with the respective spin susceptibilities giving a common g value [20] :…”
Section: Figmentioning
confidence: 99%
“…Indeed, a few percent of chemical impurities have the same effect on the conductivity as defects created by irradiation [5,6]. On the other hand, alloying with isostructural molecules results in only a smooth variation of the conductivity, especially for low concentrations [20].…”
mentioning
confidence: 99%